Faktor yang Memengaruhi Kejadian Tuberkulosis Paru pada Penderita Diabetes Mellitus di Rumah Sakit X - Yosephine, Michel Kezia; Hardy, Fathinah Ranggauni; Wenny, Dwi Mutia; Nurrizka, Rahmah Hida; Pulungan, Rafiah Maharani (Poltekkes Kemenkes Tanjung Karang, 2021)
People with diabetes mellitus are at higher risk for developing active tuberculosis. The diabetes mellitus epidemic has increased the incidence of lung tuberculosis. The purpose of this study is to determine factors that affect the incidence of lung tuberculosis in diabetic patients at â€œXâ€ hospital in 2020. The method used analytic with case-control research design. The sampling technique is purposive sampling and involved 110 respondents using a sample ratio of 1:1 for the case and control groups. The data source in this study is secondary data from the patientâ€™s medical record. The analysis used is chi-square and logistic regression. The variables studied are age, sex, employment, nutritional status, HbA1C levels, and duration of having diabetes mellitus. The result show factors associated with tuberculosis patients are age (p-value=0,038; OR=3,068), sex (p-value=0,022; OR=2,625), nutritional status (p-value=0,013; OR=0,352), and HbA1c level (p-value=0,046; OR= 2,440). Based on the results of the multivariate analyses factor that has more effects is the HbA1C level (Adjusted OR= 3,141; 95%CI= 1,299-7,594). Recommended for diabetic patients to do a healthy diet, regular exercise, comply with diabetes mellitus treatment, and regularly check blood glucose to maintain normal blood glucose levels.Â